Audit Quality Measurement Criteria - Hamidreza Rezaei; Mahdi Moradi; Mohammad Ali Bagherpour Velashani; Mahdi Jabbari noghabi (پژوهش‌های تجربی حسابداری)
Due to different definitions and views of audit quality, different criteria are used to measure it, and most of the criteria used refer to one of the dimensions of audit quality and may have errors. In this research, the measurable and accessible criteria for assessing audit quality from the users' point of view have been identified. To achieve the goal of the research, 18 members of public accountants, financial managers, investors, and bank facility managers were interviewed, and the foundation data method and thematic analysis were used to collect, classify, and analyze the collected data. Interviews and criteria were classified into four main categories platforms (characteristics of the owner's company), input factors (characteristics of the audit firm), processes, and results. The number of main categories presented for the desired classifications was presented in total 8 categories and 67 sub-categories and measurable indicators were proposed for the main categories. Also, after presenting the main, sub-categories and indicators, the impact of each indicator on audit quality was presented by the interviewees. Most of the interviewees talked about the impact of the characteristics of the employer's environment on the quality of the audit, which unfortunately has been neglected to measure the quality of the audit. Also, the indicators proposed by the interviewees, unlike most of the indicators proposed in the research of this field, were specific to each audit work and change with the change of the company without changing the audit and are no longer specific to the characteristics of the auditor and with the information available to most users. It can be measured